Islamic Marketing Strategy on Beef Sales at Muka Market, Cianjur Regency - Lestari, Linda (Journal of Economicate Studies, 2025)
The level of community need for animal food is still quite high because animal food is one of the main ingredients in meeting the nutritional needs of the community. This article examines how the implementation of an Islamic-based marketing strategy is carried out by one of the traders at the Muka Market, Cianjur Regency. The research method used is qualitative with the type of field research. Sources of data obtained from primary data and secondary data, with data collection used are interviews, document review, and observation, as well as analysis techniques with descriptive analysis method. The results of the discussion that in general H.Salim's trading kiosks have implemented the sharia concept and implemented sharia-based marketing strategies well following the example of the Prophet Muhammad SAW. In analyzing the marketing strategy carried out using a SWOT analysis (strengths, weaknesses, opportunities, and threats), the results obtained are that several things must be improved, such as management patterns and promotional strategies to maximize the level of profits obtained.